Synthesis a group of 5(6)‐substituted benzimidazole Zn(II) and Co(II) complexes and investigation their cytotoxic and antimicrobial activities. (17th February 2022) - Yılmaz, Ülkü; Apohan, Elif; Küçükbay, Hasan; Yılmaz, Özgür; Tatlıcı, Eray; Yeşilada, Özfer
Abstract: A series of 5(6)‐substituted benzimidazole ligand‐zinc(II) and cobalt(II) complexes were synthesized and characterized by 1 H, 13 C NMR, IR, CHN analysis techniques. In vitro, anticancer and antimicrobial activities of ligand and complexes were evaluated. The cytotoxic activities of compounds were investigated against the human lung adenocarcinoma (A549) cell lines and healthy human lung bronchial epithelium (BEAS2B) cells. Compounds 1, 6, and 8 were observed to exhibit higher cytotoxic activity than the others at the 72nd hour. Also, the compounds showed varying degrees of antimicrobial activity against the microorganisms used. Compounds 1, 5, and 8 were most effective against standard strains Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATCC 29213. As for the antifungal activity, compounds 1, 5, 6, and 8 showed high antifungal activity against the yeast type fungi Candida albicans ATCC 90028 and Candida tropicalis . Abstract : 5(6)‐Methyl or nitro benzimidazole ligands containing 1‐(4‐chlorobenzyl) or 1‐(4‐bromobenzyl) groups and their zinc(II) and cobalt(II) complexes were synthesized. Antimicrobial and anticancer activities of ligands and metal complexes were investigated. According to the results, the compounds containing a methyl group in the 5(6) position of benzimidazole showed higher cytotoxic and antimicrobial activities